A Comparison of Feeding Behaviour and Preferences of Native and Non-native Invasive Apple Snail in Thailand - Piyaruk Pradabphetrat (Science Faculty of Chiang Mai University, 2019)
Feeding behaviour is one behavioural trait which may contribute to the success of non-native invasive species in new environments. Here, we examine feeding behaviour of the native apple snail (Pila angelica) and the non-native invasive apple snail (Pomacea canaliculata) when tested separately and together to determine consumption rates. We found that the invasive apple snail had significantly higher consumption rates than the native apple snail both when tested separately and when tested together. In addition, it was found that consumption rate was correlated with shell size of P. canaliculata when tested separately. To predict the potential impact of apple snails on aquatic and agricultural plants, we tested the feeding preferences of Pila pesmei and P. canaliculata by using the hydrilla plant (Hydrilla verticillata) and rice (Oryza sativa) in food-choice experiments. It was found that P. canaliculata preferred to consume O. sativa over H. verticillata. Moreover, P. canaliculata consumed more in all plant species compared to P. pesmei. These findings may elucidate how P. canaliculata becomes a successfully established species and affects native apple snail populations.